Air‐Stable Organic Solar Cells Using an Iodine‐Free Solvent Additive. Issue 21 (9th August 2016) - Lee, Seongyu; Kong, Jaemin; Lee, Kwanghee
Abstract : It is observed that degradation of organic bulk heterojunction is directly associated with degradation of solvent additive, 1, 8‐diiodooctane. The iodide impurities released from 1, 8‐diiodooctane react with fullerenes, making fullerene‐iodide intermediate compounds which lead to fullerene oxidation and efficiency drop, irrespective of photooxidation of polymer in polymer/fullerene bulk heterojunctions. Replacing the additive with an iodine‐free reagent significantly elongates a device lifetime.